2016
DOI: 10.3390/ijms17040510
|View full text |Cite
|
Sign up to set email alerts
|

Power Frequency Magnetic Fields Affect the p38 MAPK-Mediated Regulation of NB69 Cell Proliferation Implication of Free Radicals

Abstract: The proliferative response of the neuroblastoma line NB69 to a 100 µT, 50 Hz magnetic field (MF) has been shown mediated by activation of the MAPK-ERK1/2 pathway. This work investigates the MF effect on the cell cycle of NB69, the participation of p38 and c-Jun N-terminal (JNK) kinases in the field-induced proliferative response and the potential involvement of reactive oxygen species (ROS) in the activation of the MAPK-ERK1/2 and -p38 signaling pathways. NB69 cultures were exposed to the 100 µT MF, either int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 80 publications
(123 reference statements)
7
33
0
Order By: Relevance
“…A 12-day exposure to a 50 Hz, 1 mT ELF-MF has been reported to increase SIRT1 level in mesenchymal stem cells from adult bone marrow 46 , whereas transcranial magnetic stimulation with an ELF field has been proven to upregulate NRF2 in a rat model of Huntington’s disease 45 . Since SIRT1 and SIRT3 overexpression has been previously shown to elicit cytoprotective action in SH-SY5Y against oxidative stress-promoting challenges 70 , 71 , the distinctive pattern of biochemical and molecular responses we observed in MF-exposed cells corroborate the idea that the interaction between ELF-MF and biosystems may activate redox-responsive processes, as hypothesized by us and others 19 , 20 , 25 , 26 , 72 , 73 .…”
Section: Discussionsupporting
confidence: 87%
“…A 12-day exposure to a 50 Hz, 1 mT ELF-MF has been reported to increase SIRT1 level in mesenchymal stem cells from adult bone marrow 46 , whereas transcranial magnetic stimulation with an ELF field has been proven to upregulate NRF2 in a rat model of Huntington’s disease 45 . Since SIRT1 and SIRT3 overexpression has been previously shown to elicit cytoprotective action in SH-SY5Y against oxidative stress-promoting challenges 70 , 71 , the distinctive pattern of biochemical and molecular responses we observed in MF-exposed cells corroborate the idea that the interaction between ELF-MF and biosystems may activate redox-responsive processes, as hypothesized by us and others 19 , 20 , 25 , 26 , 72 , 73 .…”
Section: Discussionsupporting
confidence: 87%
“…Some available studies provide hints that MF also acts like a mild stressor. For example, after MF exposure (100 µT, 50 Hz) an induced transient activation of p38, JNK and ERK1/2 was shown in NB69 cells accompanied by changes in the cell cycle progression ( 73 ). The authors showed that the MF-induced proliferative effects were exerted through sequential upregulation of MAPK-p38 and ERK1/2 activation and that the upregulation likely was mediated by a ROS-dependent activation of p38.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Importantly, the activation of the MAPKs and Akt by both shortterm and long-term exposure to ELF-MF has been demonstrated [33,34]. Effects of ERKs and Akt due to short-term (30 min) exposures have been found in various systems, including HL-60, MCF7, 3Y1, HTB124, HaCaT, and NB69 cells [33][34][35][36]. Activatory phosphorylation of stress-related MAPKs, JNK, and p38 by ELF-MF has been demonstrated as well in CHL cells exposed to 50 Hz for 3 -15 min [37][38][39], and in NB69 cells exposed to 50 Hz ELF-MF for 15, 30, or 60 min [33].…”
Section: Introductionmentioning
confidence: 98%
“…Dysregulation of these five signaling pathways is involved in the induction and maintenance of many pathologies, including cancer, diabetes, and autoimmunity [18,32]. Importantly, the activation of the MAPKs and Akt by both shortterm and long-term exposure to ELF-MF has been demonstrated [33,34]. Effects of ERKs and Akt due to short-term (30 min) exposures have been found in various systems, including HL-60, MCF7, 3Y1, HTB124, HaCaT, and NB69 cells [33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation